2010
DOI: 10.5051/jpis.2010.40.4.188
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic evaluation of maxillary single-tooth implants in the esthetic zone

Abstract: PurposeThe aim of this study is to assess the influence exerted by the observer's dental specialization and compare patients' opinion with observers' opinion of the esthetics of maxillary single-tooth implants in the esthetic zone.MethodsForty-one adult patients, who were treated with a single implant in the esthetic zone, were enrolled in this study. Eight observers (2 periodontists, 2 prosthodontists, 2 orthodontists and 2 senior dental students) applied the pink esthetic score (PES)/white esthetic score (WE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 15 publications
12
90
3
Order By: Relevance
“…It has been reported that the use of oral photographs in the assessment of single-tooth peri-implant soft tissue permitted accurate and objective measurements 3435. In this study, we have reported a strong correlation between the esthetic evaluation performed by the dentist (PES/WES) and by the patient (VAS), which was comparable with the results of the study performed by Cho et al20 Cho et al compared patient's perception on aesthetic appearance with the perception of five trained prosthodontists and concluded that professionals might be much more critical towards the aesthetic outcome than the patients. This result was in contradiction to other studies, in which no correlation was observed 16…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It has been reported that the use of oral photographs in the assessment of single-tooth peri-implant soft tissue permitted accurate and objective measurements 3435. In this study, we have reported a strong correlation between the esthetic evaluation performed by the dentist (PES/WES) and by the patient (VAS), which was comparable with the results of the study performed by Cho et al20 Cho et al compared patient's perception on aesthetic appearance with the perception of five trained prosthodontists and concluded that professionals might be much more critical towards the aesthetic outcome than the patients. This result was in contradiction to other studies, in which no correlation was observed 16…”
Section: Discussionsupporting
confidence: 89%
“…In another study, the aesthetic implant crown index was used, and this index was related to the implant restoration itself and the surrounding soft tissues 14. The results of the present study showed that the mesial and distal papilla scores were slightly less favorable (1.5 and 1.4, respectively) in comparison with other studies 1620. It is difficult to compare the papilla level between the studies because each study followed a different surgical protocol.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Fuhauser et al reported that orthodontists were the most critical among twenty observers (five prosthodontists, five oral surgeons, five orthodontists, and five dental students) who assessed the PES of the soft tissue of 30 single-tooth implant crowns [29]. Cho et al mentioned that periodontists were the most generous and prosthodontists were the most critical of eight observers (two periodontists, two prosthodontists, two orthodontists, and two dental students) who assessed the PES and WES of 41 implant-supported single restorations [30]. Careful attention should be paid to the assessments of different observers, especially in different fields, when using the PES and WES.…”
Section: Objective Evaluationmentioning
confidence: 98%
“…The PES is a composite score of the tooth volume/outline [2], mesio-gingival papilla, distal gingival papilla, labial margin curvature, labial edge height, and the color and texture of soft tissue.…”
Section: How Does One Evaluate Soft Tissue Esthetics?mentioning
confidence: 99%